Promoting Hokien dialect at the workplace: a survey on non-Chinese communities in Peninsular Malaysia - Ng, Boon Sim; Chan, Swee Heng (Penerbit UTM Press, 2017)
The Chinese community in Malaysia is made up of at least 6 sub- ethnic groups which are distinguished by their dialects. The main objective of this study is to identify the role of Hokkien dialect in promoting effective communication in the work place among non- Chinese communities from different social background. This study also explores the level of interest of non- Chinese communities in pursuing the dialect as well as the needs of related expertise areas that required Chinese dialects competency in the work place in Malaysia. The methodology used in this study includes interviews. Sets of questionnaires are distributed to 3 groups of informant I.e. civil servants, workplace employees and self- employed group. The significance of the study is to develop understanding at the work place as well as to strengthen ethnic relationship between Chinese and non- Chinese communities in Malaysia. It is also hoped that the study will contribute to government agencies, language planners and researchers in the field.